Analisis Soft Skill Kesiapan Kerja Mahasiswa Tingkat Akhir Jurusan Pendidikan IPS - Visia Riyanita; Yusmansyah Yusmansyah; Ratna Widiastuti (ALIBKIN (Jurnal Bimbingan Konseling), 2018)
The problem in this research was final-year student’s employability soft skill of social education major. This study aims to provide a descriptive description of final-year student’s employability soft skill of social education major, Faculty of Teacher Training and Education, University of Lampung. The research method used in this research was descriptive quantitative. The research samples were taken from 20% of the population which is 192 students, it was using simple random sampling technique. Data collection techniques used in this research was employability scale. The result showed that 76% final-year students in social education major, Faculty of Teacher Training and Education, University of Lampung have medium level of employability. The result showed that final-year students in social education major, Faculty of Teacher Training and Education, University of Lampung have medium level of employability soft skills, consists of possitive self concept, self control, social skill, communication skill, dan high order thinking skill. The lowest of employability skills on final-year students majoring in social science education is self control. The highest of employability skills on final-year students majoring in social science education is possitive self concept.Pendidikan IPS Permasalahan dalam penelitian ini adalah soft skill kesiapan kerja pada mahasiswa tingkat akhir Jurusan IPS. Penelitian ini bertujuan untuk memberikan gambaran deskriptif mengenai soft skill kesiapan kerja pada mahasiswa tingkat akhir Jurusan IPS FKIP Universitas Lampung. Metode penelitian yang digunakan pada penelitian ini bersifat deskriptif kuantitatif. Sampel penelitian diambil dari 20% dari populasi yaitu sebanyak 192 mahasiswa, sampel diambil dengan menggunakan teknik simple random sampling. Teknik pengumpulan data menggunakan skala kesiapan kerja. Hasil penelitian menunjukkan bahwa 76% mahasiswa tingkat akhir jurusan pendidikan IPS FKIP Universitas Lampung memiliki tingkat kesiapan kerja yang sedang. Mahasiswa tingkat akhir Jurusan IPS FKIP Universitas Lampung memiliki tingkat soft skill kesiapan kerja yang sedang, yang terdiri dari possitive self concept, self control, social skill, communication skill, dan high order thinking skill. Soft skill kesiapan kerja pada mahasiswa tingkat akhir jurusan pendidikan IPS yang rendah yaitu self control. Soft skill kesiapan kerja pada mahasiswa tingkat akhir jurusan pendidikan IPS yang tinggi yaitu possitive self concept.Kata kunci: bimbingan konseling, kesiapan kerja, soft skills, ips